Regional convergence in CEE before and after the Global Financial Crisis - L. I. Smirnych; Andreas Wörgötter (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2021)
In this study we analyze the convergence of GDP per capita from 2000 to2013 (current prices and euro exchange rates) for eight countries (Czech Republic, Slovakia, Slovenia, Hungary, Poland, Estonia, Latvia and Lithuania) of the European Union (CEE8). Some convergence indicators are also calculated for the CEE8 as a whole. The main purpose of this study is to shed some light on the impact of the Global Financial Crisis (GFC) on regional convergence in advanced emerging countries, like the CEE8. The main result of random effects panel regressions for unconditional beta-convergence is that significant convergence is found for the whole period from 2000-2013, but not for sub-periods on either end of the sample, except for Hungary and Poland. This means that convergence in most CEECs is only significant if the GFC is included in the estimation period. The role of capital regions for the convergence process is an item for future research.
Keywords: 330; Wirtschaftliche Konvergenz; Räumliche Verteilung; Bruttoinlandsprodukt; Gini-Koeffizient; Konzentrationsmaß; Finanzkrise; Osteuropa